Technological Progression of Graphic Design in Pakistan: A comprehensive Examination of Industry’s Evolution - Mehrbano Khattak; Naima Muzaffar (Journal of Design and Textiles, 2023)
The field of graphic design has gone through a process of continuous evolution and expansion with innovations in technology over the years, which transformed and developed a new perception of this field both for the public and for the graphic designers as well. This paper attempts to study the changing trends and evolution of the field of graphic design in Pakistan in light of the advancements happening in the field of technology. The emergence of evolving technology has given graphic designers new avenues to change the face of how design is perceived by introducing new possibilities for creative outcomes.